Pembinaan Self Image Berbasis Nilai-nilai Kristiani untuk Meningkatkan Kualitas Diri Siswa SMPK 2 Harapan Untal-Untal - Muhadi Muhadi; Ni Nyoman Fransiska; Gusti Ngurah Sukadana; Cajenino Cajenino; Adam Adam (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2026)
Adolescence is a critical phase in the formation of self-identity, which is heavily influenced by self-image. Students at SMPK 2 Harapan Untal-Untal Bali exhibit signs of low self-image, reflected in feelings of inferiority and an inability to fully realize their potential, a situation further exacerbated by exposure to social media and its unrealistic standards. The objective of this Community Service (PkM) activity is to build a foundation for a healthy self-image among adolescent students through the integration of psychological approaches and Christian values. The partners of the activity were 60 students and 12 teachers and staff at SMPK 2 Harapan Untal-Untal Bali. The methods used were integrative, including interactive lectures, biblical reflection based on the Imago Dei concept (Gen 1:27), small group discussions, and self-affirmation exercises based on God’s Word. The results showed an increase in students’ understanding of their identity in Christ, with 85% of participants stating they were better able to accept themselves. The impact of this activity included increased awareness among teachers regarding their role in guiding students’ identity development, as well as the creation of a school culture that better supports the growth of healthy self-esteem.